Effects of Seedbed Density on Seedling Morphological Characteristics of four Broad leaved Species - Yucedag, C.; Gailing, O. (Inst Nacional Investigacion Technologia Agraria Alimentaria, 2012)
The aim of this study was to investigate the effects of seedling spacing on morphological characteristics of one year-old Amygdalus communis L., Prunus avium L., Pyrus elaeagnifolia Pall. and Eriolobus trilobatus (Poiret) Roemer seedlings under nursery conditions. Seedlings were grown in completely randomized blocks with four replications. Seedbeds were 1.2 m wide with 5 rows each 20 cm apart. Within-row spacings were chosen as 4, 8 and 12 cm to analyze the effect of seedlings density on growth performance. Seedling spacing significantly affected root collar diameter, shoot height, tap root length and number of fine roots in A. communis and P avium, but not in P elaeagnifolia and E. tribolatus. Additionally wider seedling spacings resulted in larger seedlings in A. communis and P avium. In conclusion, it would be beneficial to use wider seedling spacing in order to obtain better seedling growth in A. communis and P avium. Larger seedlings could also provide significant advantages because of reduced cultural activities and an expected higher growth and survival rate.
Keywords: Amygdalus Communis; Eriolobus Trilobatus; Morphology; Prunus Avium; Pyrus Elaeagnifolia; Seedling Performance; Seedling Spacing